Employment challenge : an agenda for global action (UNDP New YorkUS, 1994)
Looks at the nature of the employment problem and its macroeconomic solution. Tries to identify policies that will do most to create decent jobs in sufficient numbers.
Policy paper commissioned by UNDP for the World Summit for Social Development